Legal Certainty of a Sales and Purchase Agreement Deed Made Without Being Read by and Not Signed Before a Notary - Hanip, Furqon; Martanti, Yurisa; Kadir, Taqiyuddin (PT FORMOSA CENDEKIA GLOBAL, 2025)
Notaries play a crucial role in ensuring the validity of legal transactions through authentic deeds with strong evidentiary power. However, procedural violations such as deeds not being read aloud or signed before the notary contradict Article 16 paragraph (1) letter m of Law No. 2 of 2014 on the Notary Position and may render the deed legally flawed, reducing it to the status of a private deed. This study aims to examine legal remedies available to the parties and the certainty provided by such flawed deeds. Using a normative legal research method supported by literature review, statutory analysis, and interviews with legal practitioners, the study finds that such deeds undermine legal certainty, and recommends stronger disciplinary enforcement against violating notaries.